Republic of Georgia : Fifth Review Under the Extended Arrangement, Requests for Waivers of Nonobservance of Performance Criteria, Modification of Performance Criteria, and an Extension of the Arrangement and Rephasing of Access-Press Release; Staff Report; and Statement by the Executive Director for Georgia. (IMF Staff Country Reports; Country Report ;, 2019)
This paper discusses Republic of Georgia's Fifth Review Under the Extended Arrangement, Requests for Waivers of NonObservance of Performance Criteria, Modification of Performance Criteria, and an Extension of the Arrangement and Rephasing of Access. Georgia's gross domestic product (GDP) growth remains on track to reach 4.6 percent despite the ban on direct flights from Russia. Strong revenue growth has more than offset higher-than-envisaged capital spending, and the 2019 fiscal deficit is likely to be lower than projected at the Fourth Review. The 2020 budget implies a neutral fiscal stance; spending on education and social benefits is expected to rise, while overall current primary spending would remain unchanged. Medium-term fiscal plans are anchored at keeping net debt below 45 percent of GDP. The central bank should maintain a tightening bias until inflation expectations are firmly anchored. The planned emergency liquidity assistance and bank resolution framework will strengthen financial stability. Decisive implementation of structural reforms is critical to support higher and more inclusive growth. Advancing education reform, adopting the insolvency framework, developing the local capital market, and judiciary reform will further improve the business environment and support private investment.